Determining Tofu Production Volume Using Fuzzy Logic Mamdani Method - Jason Timoty Wijaya; Chika Hayya Sabillah; Muhammad Faiz Assariy; Daffa Zulqisthi; Vira Aulia Puteri; Salsabilla Kansa Ismail; Rizqi Hasna Amalia; Riris Rahayu; Hilda Aulia Ainussyfa; Evy Apriliani; Annisa Royani; Mrr. Lukie Trianawati (Batrisya Education, 2025)
This research focuses on determining the amount of tofu production based on the amount of consumer demand and the amount of raw material inventory. Optimization of daily tofu production is a difficult problem due to uncertainty of supply an demand for tofu. The method used in this research is the fuzzy logic method which is one of the effective rule-based approach methods to determine the volume of tofu production. In this research, the data used is taked based on the results of previous research. The final results obtained in this study, namely the determination of the volume of tofu production based on the amount of consumer demand and the amount of raw material inventory is still less effective. This is because the amount of consumer demand received and the amount of raw material inventory available with the volume of tofu production produced is still not appropriate